Prevalência, distribuição espacial e fatores de risco para cisticercose bovina no estado de São Paulo - Ferreira, Marlon Martins; Revoredo, Thais Buranello; Ragazzi, Juliana Pistore; Soares, Vando Edesio; Ferraldo, Antonio Sergio [UNESP]; Mendonca, Rafael Paranhos de; Zanetti Lopes, Welber Daniel (Revista Pesquisa Veterinaria Brasileira, 2014)
This study aimed to determine the prevalence and geographical distribution as well as the factors and areas of risk associated with bovine cysticercosis in the State of Sao Paulo. 34.443 cattle, males and females with ages from 18 to 60 months were inspected. The animals were from 97 cities in the state of Sao Paulo and identified and slaughtered in the period October 2010 to August 2011, in a refrigerator located in Ipua - SP, under the supervision of SIF 1387. The state of Sao Paulo was divided into regional centers, and the data of the municipalities belonging to its core, were grouped according to the Department of Agriculture and Food Supply of Sao Paulo, totaling 13 cores studied. Based on these results, we can conclude that of the 97 cities analyzed, cattle were found positive for the disease in 86. The average prevalence of bovine cysticercosis in the state of Sao Paulo was 4.80 %, while the core inflation Franca and Barretos were the ones with the highest number of cases illness during the analysis period. Moreover, the largest number of cases in these core coincided with the lowest human development index covering education, with the largest acreage of coffee (core Franca) and also as the largest area of cane sugar grown (core Barretos) in these locations, which in turn may indicate that the presence of labor, temporary labor in rural areas, combined with socioeconomic/cultural factors might contribute to the spread and establishment of bovine cysticercosis in these areas.

O presente trabalho teve como objetivos determinar a prevalência, a distribuição geográfica bem como os fatores e áreas de risco associados à cisticercose bovina no Estado de São Paulo. Foram inspecionados 34.443 animais, machos e fêmeas e com faixas etárias variando entre 18 a 60 meses. Os bovinos eram procedentes de 97 municípios do Estado de São Paulo, devidamente identificados e abatidos no período de outubro de 2010 a agosto de 2011, em um frigorífico localizado na cidade de Ipuã-SP, sob supervisão do SIF 1387. O estado de São Paulo foi dividido em núcleos regionais, e os dados dos municípios pertencentes ao respectivo núcleo, foram agrupados, conforme a Secretaria de Abastecimento e Agropecuária de São Paulo, totalizando 13 núcleos estudados. Com base nos resultados encontrados, pode-se concluir que dos 97 municípios analisados, foi possível encontrar bovinos positivos para a enfermidade em questão em 86. A prevalência média de cisticercose bovina no estado de São Paulo foi de 4,80%, sendo que os núcleos de Franca e Barretos foram os que tiveram maior número de casos da enfermidade durante o período analisado. Além disso, o maior número de casos nestes núcleos coincidiu com o menor índice de desenvolvimento humano referente à educação, com a maior área de plantio de café (núcleo de Franca) e também como a maior área de cana-de-açúcar cultivada (núcleo de Barretos) nestes locais, o que por sua vez pode indicar que a presença da mão-de-obra temporária no meio rural, aliado a aspectos socioeconômico/cultural, pode estar contribuindo para a disseminação e estabelecimento da cisticercose bovina nestas áreas.
Prevalence, spatial distribution and risk factors for cattle cysticercosis in the state of Sao Paulo, Brazil
Keywords: Cysticercus bovis; Bovine cysticercosis; Georeferencing; Taenia saginata; Cysticercus bovis; Cisticercose bovina; Georeferenciamento; Taenia saginata